The phenomenon of polygamy in the Palestinian Personal Status low and its legal position - Dala’a, Muwaffaq Muhammad Abdo; Abu Freih, Sami Jarad Sweilem (Journal of Economic, Administrative and Legal Sciences, 2022)
In this study, the researcher discusses the issue of "The Phenomenon of Polygamy in the Personal Status Law in the Palestinian Interior and the Legal position towards this phenomenon". This is by reviewing how the personal status law in the Palestinian interior deals with the phenomenon of polygamy and its opinion towards it, the opinion of women's associations and institutions in the Palestinian interior towards this phenomenon, and the impacts of the prevention of this phenomenon on the economic and demographic aspects.The research is concluded with many results, including:1- people have considered that the Personal Status Law does not include a clear position on the phenomenon of polygamy.2- Although the Personal Status Law criminalizes the phenomenon of polygamy under the influence of multiple Israeli laws, no one, on the other hand, cares about these laws. This is especially because of that there are many cases of polygamy, divorce, and marriage that take place outside the framework of this law. Therefore, many people marginalize and do not pay attention to it.3- Many human rights and feminist associations and institutions have clearly tried to prevent polygamy. After many years of struggle for that, these institutions have succeeded in approving an amendment to the law in 2001.The study also recommended the following:1- The necessity of putting pressure on Israel to recognize Arab towns and villages and integrate them with the Israeli economy and build an infrastructure for them.2- The necessity for women’s rights institutions and associations in Arab regions, towns and cities to exert pressure on Israel so that it does not interfere in the laws relating to the personal status of Arabs and not to append any of them to Israeli courts.
Keywords: polygamy; personal status law; the Palestinian interior